Analysis of Service Quality to Increase Customer Satisfaction of Libro Café - Hendy Tannady; Ananta Aditia; Bima Bhadra; Clara Cung (PT. EQUATOR SINAR AKADEMIA, 2023)
This research was conducted using a quantitative survey method which managed to collect 30 respondents who were students of one private university in Banten. The goal of this study is to evaluate how satisfied customers are with the level of service offered by Libro Café, a café that is housed within a university. The first and ninth indicators are both in quadrant I, which represents areas that are very important yet nevertheless perform poorly. This cafe should pay attention to and develop these two aspects so that customers can feel satisfied with the queuing system and the friendliness of Libro cashiers and baristas. Then in quadrant II, there are the second and third indicators which discuss the payment system or payment methods and the cafe area's cleanliness. Being in the second quadrant denotes significant relevance and performance. It is advised that the café continue with this because it is a very wonderful thing. It is in quadrant III, which indicates that its importance and performance are modest, there is the tenth indicator. This indicator discusses Libro café, which sells products at reasonable and affordable prices. Even though the urgency level is not that important, this indication needs to be taken into account and developed because it is a part of quadrant III. Last but not least, quadrant IV, which is low in relevance but high in performance, there are indicators 4 to 8, which are in this quadrant IV. This is also a good thing.